Offerings made to the goddess - Mumbai Archive Project Team (Jio Institute, 2024)
Various offerings made by the family and by villagers are assembled in front of the Goddess. Some of these items, like bananas, rice grains, and coconuts, are offered for a bountiful harvest, while others, such as boxes of sweets, are given as tokens of thanksgiving for the fulfilment of a wish. Some of the offerings may be used to prepare the naivedya (sacred food offerings), which is distributed as prasad (blessed food) after the puja (prayers of devotional homage) ceremony is concluded.